Heterotrimeric coiled-coils as viral fusion protein mimics - Johnson, Dana E., author; Kennan, Alan J., advisor; Finke, Richard G., committee member; Peersen, Olve B., committee member; Rovis, Tomislav, committee member; Shores, Matthew P., committee member (Colorado State University. Libraries, 2010)
The a-helical coiled-coil, formed by the association and supercoiling of two or more a-helices, is a ubiquitous protein structure that mediates a wide range of biological activity. It is characterized by a heptad repeat of amino acids that serve to form both the hydrophobic core and electrostatic interfaces of the coiled-coil. Previous work in our lab showed the viability of designing a self-assembling heterotrimeric coiled-coil by sole manipulation of the hydrophobic core. This technique utilized a steric matching approach whereby one large side chain packed against two small ones. An added benefit to this type of control is that it allowed the freedom to explore additional interactions specific to the electrostatic interface. Many enveloped viruses, including HIV-1, incorporate trimeric coiled-coils in their fusion proteins, and, consequently, are involved in the pathway to infection. Through interactions at the electrostatic interfaces of the coiled-coils, these fusion proteins form a six-helix bundle called a trimer-of-hairpins. The formation of this structure is a precursor to membrane fusion of the viral and host cells, and, as a result, it has become a therapeutic target. The steric matching technique developed in our lab allows us to graft key contacts from the native 111 sequences onto a stable, heterotrimeric system and construct a mimic of the trimer-of-hairpins, as was done with HIV-I previously in our lab. The work that follows shows that a viable mimic of the Human Respiratory Syncytial Virus is also possible. A stable, self-assembling mimic was designed, synthesized and validated through various spectroscopic methods. Additionally, a mutant study was conducted to further refine our knowledge of the importance of the residues thought to be key to the formation of the trimer-of-hairpins. Other work was performed extending the process to the Human T-cell Leukemia Virus, bringing the possibility of a complete and stable mimic ever closer.
Covers not scanned.
Keywords: Mimicry (Chemistry); Chemistry, Organic; Respiratory syncytial virus